SOCIAL CAPITAL MANIFESTED IN PESANTREN: The Role and Contribution of Kiai Toward Padepokan Dimas Kanjeng’s Victims - Ahmad Fauzi (AL-TAHRIR, 2020)
Abstract: This research, praxis aims to describe and interpret various roles and social contributions of the kiai to victims of Dimas Kanjeng in Probolinggo. Sociologically, the existence of kiai in the midst of society occupies the most strategic position, even all forms of social action and advice are used as references and legitimacy for various social problems. Therefore, the presence of the kiai is understood as a pioneer of change in both the religious, moral, social and cultural fields of all domestic and social domestication (social and cultural domestication), especially for victims of Dimas Kanjeng. In this context, the existence of the kiai is an important part in providing enlightenment to overcome various problems that are happening, as a form of social change for victims of Dimas Kanjeng. Thus, to interpret and interpret the roles and social actions of the kiai, the researcher uses Pierre Bourdieu's social practice theory, between Habitus x Modal + Domain = Practice, with a qualitative approach and type of case study research. In praxis, this study produced several findings, including; 1) the presence of kiai and pesantren basically cannot be separated from scientific genealogy which is built through the Koran and al-Hadith, as core beliefs and core values, so that it becomes a social capital of the kiai (social capital) to practice social (social practice) and bring about changes in both the religious, moral and social fields, by transmitting universal religious values (kaffah), the view is expected to influence and inspire the thinking and social behavior of the community, especially for victims of Dimas Kanjeng, to shape individual piety and social piety; 2) the kiai's approach to social change, including; cultural approach, through a process of guidance regarding understanding Islamic teachings; a cultural approach, the involvement of the kiai in various socio-religious organizations becomes the main capital to influence the thinking and social behavior of other individuals; 3) various social contributions of the kiai include several aspects; kiai as social change, social cohesion, social harmonization; purification of the soul (tazkiyyat al-nafs) and moral fortifications in maintaining social integrity. الملخص: يهدف هذا البحث العملي إلى وصف وتفسير الأدوار والمساهمات الاجتماعية المختلفة للشيوخ / العلماء لضحايا ديماس كانجينج في بروبولينجو. من الناحية الاجتماعية ، يحتل وجود العلماء / الشيخ في وسط المجتمع المكان الأكثر استراتيجية ، حتى يتم استخدام جميع أشكال العمل الاجتماعي والمشورة كمراجع وشرعية لمختلف المشاكل الاجتماعية. لذلك ، يُفهم وجود العلماء / الشيخ على أنه رائد التغيير في كل من المجالات الدينية والأخلاقية والاجتماعية والثقافية لجميع التدجين الاجتماعي والثقافي ، وخاصة بالنسبة لضحايا ديماس كانجينج. في هذا السياق ، يعد وجود العلماء / الشيخ جزءًا مهمًا في توفير التنوير للتغلب على المشكلات المختلفة التي تحدث ، كشكل من أشكال التغيير الاجتماعي لضحايا ديماس كانجينج. وبالتالي ، لتفسير الأدوار والإجراءات الاجتماعية للعلماء / الشيخ ، يستخدم الباحث نظرية الممارسة الاجتماعية لبيير بورديو ، بين habitus x modal + domain = Practice، مع نهج نوعي ونوع من أبحاث دراسة الحالة.  في الممارسة ، أنتجت هذه الدراسة العديد من النتائج ، بما في ذلك ؛ 1) لا يمكن فصل وجود العلماء والشيوخ والبيزنرة في الأساس عن علم الأنساب المبني من خلال القرآن والحديث ، كمعتقدات وقيم أساسية ، بحيث يصبح رأس المال الاجتماعي للكيي لتنفيذ الممارسات الاجتماعية وإحداث التغيير في المجال الديني ، من الناحية الأخلاقية والاجتماعية ، من خلال نقل القيم الدينية العالمية (الكفة) ، من المتوقع أن تكون هذه النظرة قادرة على التأثير وإلهام الفكر والسلوك الاجتماعي ، وخاصة لضحايا ديماس كانجينج ، لتشكيل التقوى الفردية والتقوى الاجتماعية ؛ 2) نهج العلماء / الشيخ في إحداث تغييرات اجتماعية ، بما في ذلك ؛ النهج الثقافي ، من خلال عملية الإرشاد بشأن فهم التعاليم الإسلامية ؛ من خلال نهج ثقافي ، تصبح مشاركة الكيان في مختلف المنظمات الاجتماعية الدينية هي العاصمة الرئيسية للتأثير على التفكير والسلوك الاجتماعي للأفراد الآخرين ؛ 3) تشمل المساهمات الاجتماعية المختلفة للشيوخ عدة جوانب ؛ العلماء / الشيخ كتغيير اجتماعي وتماسك اجتماعي ومواءمة اجتماعية ؛ تطهير الروح (تزكية النفس) والتحصينات الأخلاقية في الحفاظ على النزاهة الاجتماعية. Abstrak: Penelitian ini praksis bertujuan untuk mendeskripsikan dan menginterpretasikan berbagai peran dan kontribusi sosial kyai kepada para korban Dimas Kanjeng di Probolinggo. Secara sosiologis, keberadaan kiai di tengah-tengah masyarakat menempati posisi paling strategis, bahkan semua bentuk aksi dan saran sosial digunakan sebagai referensi dan legitimasi untuk berbagai masalah sosial. Oleh karena itu, kehadiran kiai dipahami sebagai pelopor perubahan baik dalam bidang agama, moral, sosial dan budaya dari semua domestik dan sosial domestikasi (sosial dan budaya domestikasi), terutama untuk para korban Dimas Kanjeng. Dalam konteks ini, keberadaan kiai merupakan bagian penting dalam memberikan pencerahan untuk mengatasi berbagai masalah yang sedang terjadi, sebagai bentuk perubahan sosial bagi para korban Dimas Kanjeng. Dengan demikian, untuk menafsirkan dan menafsirkan peran dan tindakan sosial kiai, peneliti menggunakan teori praktik sosial Pierre Bourdieu, antara Habitus x Modal + Domain = Praktek, dengan pendekatan kualitatif dan jenis penelitian studi kasus. Dalam praksis, penelitian ini menghasilkan beberapa temuan, termasuk; 1) kehadiran kyai dan pesantren pada dasarnya tidak dapat dilepaskan dari silsilah ilmiah yang dibangun melalui Alquran dan al-Hadis, sebagai keyakinan inti dan nilai-nilai inti, sehingga menjadi modal sosial kiai (modal sosial) untuk mempraktikkan sosial (praktik sosial) dan membawa perubahan baik dalam bidang agama, moral dan sosial, dengan mentransmisikan nilai-nilai agama universal (kaffah), pandangan ini diharapkan dapat mempengaruhi dan menginspirasi pemikiran dan perilaku sosial masyarakat, terutama bagi para korban Dimas Kanjeng, untuk membentuk kesalehan individu dan kesalehan sosial; 2) pendekatan kiai terhadap perubahan sosial, termasuk; pendekatan budaya, melalui proses bimbingan tentang memahami ajaran Islam; pendekatan budaya, keterlibatan kiai dalam berbagai organisasi sosial keagamaan menjadi modal utama untuk mempengaruhi pemikiran dan perilaku sosial individu lain; 3) berbagai kontribusi sosial kiai mencakup beberapa aspek; kyai sebagai perubahan sosial, kohesi sosial, harmonisasi sosial; pemurnian jiwa (tazkiyyat al-nafs) dan benteng moral dalam menjaga integritas sosial.